2023
DOI: 10.1186/s13643-023-02296-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the effectiveness of the community tuberculosis care programs: a systematic review

Abstract: Background Tuberculosis is a significant global public health threat, especially in countries with limited resources. To improve tuberculosis care, the World Health Organization emphasizes the importance of considering a TB patient’s journey across a variety of connected settings and facilities. A systematic review was conducted to map previously conducted studies to identify existing community TB implementation models, their effectiveness on cost, and treatment outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“… 56 A further systematic review assessing community-based TB interventions (such as electronic medication monitors, community health worker or family direct observation therapy) in low-income and middle-income countries found these approaches may improve treatment success while also offering convenience to patients. 57 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 56 A further systematic review assessing community-based TB interventions (such as electronic medication monitors, community health worker or family direct observation therapy) in low-income and middle-income countries found these approaches may improve treatment success while also offering convenience to patients. 57 …”
Section: Discussionmentioning
confidence: 99%
“…56 A further systematic review assessing community-based TB interventions (such as electronic medication monitors, community health worker or family direct observation therapy) in low-income and middleincome countries found these approaches may improve treatment success while also offering convenience to patients. 57 Evidence on sex workers was limited to one single-arm study, and no studies were identified that focused on GRT populations. There were no studies that focused specifically on people with mental health disorder, though this was an additional risk factor in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…Damien Foundation provided motorcycles and maintenance costs, as well as monthly incentives for community volunteers, which could be costly for the NTP. However, review data show that TB treatment observed daily by community volunteers can be cost-effective [ 19 ]. At study completion, motorcycles were donated for routine programme activities.…”
Section: Discussionmentioning
confidence: 99%